SUPPORTING POSITIVE PARENTING IN COMMUNITY HEALTH CENTERS: THE ACT RAISING SAFE KIDS PROGRAM. Issue 4 (21st March 2013) - Knox, Michele; Burkhart, Kimberly; Cromly, Aaron
<x xml:space="preserve">Abstract</x> The present study involves an evaluation of the effect of the American Psychological Association's ACT Raising Safe Kids (RSK) program on parenting outcomes for families served by Community Health Centers. The ACT‐RSK program is a primary family violence and child physical abuse prevention program for parents of young children. Parents were trained in effective parenting including nonviolent discipline, child development, anger management, social problem‐solving skills, effects of violent media on children, and methods to protect children from exposure to violence. Results indicate improved nurturing and positive parenting behaviors and lower rates of psychologically and physically aggressive behavior toward children. These improvements occurred independent of children's age and prior levels of aggression. Use of this model within healthcare settings has the potential to more effectively address parents' needs for parenting guidance while reducing the likelihood of child maltreatment.